Mechanisms of Adiponectin in Regulation of Proinflammatory Cytokine Production and Migration in Macrophages - Jin X (Dove Medical Press, 2021)
Xiaogao Jin,1,2 Yanlin Wang3 1Department of Anesthesiology and Perioperative Medicine, Zhengzhou Central Hospital Affiliated to Zhengzhou University, Zhengzhou, 450007, People’s Republic of China; 2Department of Anesthesiology, The Affiliated Hospital of Guilin Medical University, Guilin, Guangxi Zhuang Autonomous Region, 541000, People’s Republic of China; 3Division of Nephrology, Department of Medicine, University of Connecticut School of Medicine, Farmington, CT, USACorrespondence: Xiaogao Jin; Yanlin Wang Email jinxiaogao@yahoo.com; yanlwang@uchc.eduIntroduction: Evidence indicate that adiponectin may exert pro-inflammatory effects on inflammatory cells. We have found that adiponectin knockout decreased inflammatory reaction and tubular damage in the ischemia-reperfusion kidney in APN-knockout mice. Globular adiponectin and full-length adiponectin (g-APN and f-APN) were used in this study to investigate the effects of adiponectin on proinflammatory cytokines production and migration in Raw 264.7 cells.Methods: Proinflammatory cytokines production was detected by real-time RT-PCR. NF-kappaB activation was interrupted through Ad-DN-IκBα or SN-50 to confirm how g-APN induces proinflammatory cytokines production. The siRNA against AdipoR1 and AdipoR2 was investigated to uncover the signaling pathway that may involve in NF-kappaB activation and migration in Raw 264.7 cells.Results: g-APN, not f-APN, was found triggering the production of inflammatory cytokine MIP-2, IL-6, TNFα, and MCP-1 in Raw 264.7 cells. NF-kappaB Inhibition by Ad-DN-IκBα expression or cell-permeable NF-κB inhibitor SN-50 could decrease NF-kappaB nuclear translocation and subsequently decrease inflammatory cytokine expression triggered by globular ANP. However, AdipoR1 and AdipoR2 were not found involved in NF-kappaB activation in this study. Full-length APN, not g-APN, was involved in the promotion of macrophage migration. The migration induced by full-length APN could be inhibited by knockdown of AdipoR1 expression with siRNA. The migration effect could also be inhibited by PI3Kγ inhibitor, AS-605240.Discussion: These results suggested that full-length adiponectin increases macrophage migration through Adiponectin-AdipoR1-PI3Kgamma signaling pathway. However, NF-κB activation induced by g-APN in this study was independent of AdipoR1 or AdipoR2. The exact signaling pathway of NF-κB activation by adiponectin should be further studied to find a new anti-inflammatory target.Keywords: adiponectin, macrophages, inflammation, migration, cytokine